POTENTIALS AND PITFALLS OF THE IMPLEMENTATION OF HYBRID LEARNING IN STRUCTURE CLASS IN RELATION TO THE STUDENTS DIGITAL LITERACY AND LEARNING ACHIEVEMENT - Vonti, Lungguh Halira; Grahadila, Leora (UNIVERSITAS PAKUAN, 2021)
The purpose of this study is to describe the potential and the pitfalls of the implementation of hybrid learning in structure class. The sampling technique used was purposive sampling since there was only one class who experienced hybrid learning in grammar class. The samples were 20 students of class D from the third semester. The research instrument was a questionnaire and also Focus Group Interview. The research method used is mixed method. The quantitative data is taken from experimental research design and is processed by using SPSS (Statistical Package for Social Science) software version 25.0. the qualitative data is taken from the questionnaire and focus group interview. The results showed the application of hybrid learning affected positively to the students score in structure class since there is significant increase of their posttest score. Based on the qualitative data, it is shown that the application of hybrid learning model has certain aspects that affect their improvement in structure class. Yet, based on the FGI, the researcher also found out some disadvantages of pitfalls of the implementation of hybrid learning.